Psychometric properties of the Turkish Adult Consumer version of the Primary Care Assessment Tool (PCAT-TR) - Tülay Lağarlı; Erhan Eser; Hakan Baydur (Turkish Society of Public Health Specialists, 2014)
Objective: To explore the psychometric properties of the Turkish version of the "Primary Care Assessment Tool (PCAT-TR). Methods: The results of this study represent 279,000 residents who were registered in 79 Family Health Centers of the Manisa city center. The sample selection used multistage cluster sampling from 80 clusters (n=800). A confirmatory approach and SEM modeling were used during both reliability (internal consistency) and validity (structural validity, such as known groups validity; convergent-divergent validity and confirmatory factor) analyses. Data analyses were done by using SPSS 15.0 and Lisrell 8.05 softwares for univariate parametric and non-parametric tests; multivariate analyses and confirmatory factor analysis were employed during statistical analyses of this study. Results: Mean age was 40.33 ± 13.85 with a female percentage of 76.7. Chronbach alpha values were also found satisfactory (0.80-0.90) for all domains and subdomains of the PCAT except for three subdomains: Coordination (information system), First contact care (access) and Comprehensiveness (service provided). CFA revealed RMSEA :0.10, CFI:0.84 (full model); and for the derivative subdomains the CFA model generated RMSEA  as 0.12, and  CFI as 0.88. Conclusion: PCAT can be used to evaluate the performance of PHC services in Turkey. The results of the ongoing and following studies are expected to reach some more information about further reliability and validity of the Turkish PCAT. Keywords: Primary care assessment, PCAT, Turkish.